ADMINISTRATIVE LAW OF THE REPUBLIC OF UZBEKISTAN: CURRENT STATE, CHALLENGES, AND DEVELOPMENT PROSPECTS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article presents a comprehensive analysis of the current state of administrative law in Uzbekistan. It highlights pressing challenges in codification, access to administrative justice, digital governance, and anti-corruption mechanisms. Through comparative and legal-institutional analysis, the study identifies practical solutions for reforming Uzbekistan’s administrative legal framework in alignment with international legal standards and democratic governance principles. Recommendations are proposed for harmonization, digital transformation, citizen engagement, and the modernization of judicial and procedural safeguards.